(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article reflects the scientific basis of intuition in the world of science, synergetic analysis, the place of memory and attention, balanced connections between the conscious and the unconscious.